MODEL PEMBELAJARAN SCRAMBLE UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS V SD NEGERI 2 PALEMBANG - Gian Handini (Jurnal Inovasi Sekolah Dasar, 2020)
The purpose of this study was to improve the social studies learning outcomes of fifth grade students of SD Negeri 2 Palembang by applying the Scramble learning model. This research is a Classroom Action Research. The subjects in this study were class V.B SD Negeri 2 Palembang, with a total of 29 students, 16 male students and 13 female students. This research was conducted in several stages, namely planning, implementing, observing, and reflecting. Data collection techniques using tests, observation and documentation. This research was conducted in three cycles, each cycle consisting of two meetings. The results of this study indicate that there is an increase in student learning outcomes and student activeness by applying the Scramble learning model. The improvement of student learning outcomes in cycle I 21 students (72.41%), cycle II 23 students (79.31%), cycle III (96.55%). While the results of observations of student learning activities increased from the first cycle of meeting 1 by 65.08%, meeting 2 65.51%, cycle II meeting 1 66.38% and meeting 2 increasing to 70.69%, and meeting III meeting 1 of 77.59% and meeting 2 increased to 84.05%. Thus it can be concluded that the application of the Scramble learning model can improve social studies learning outcomes for fifth grade students of SD Negeri 2 Palembang.Keywords: learning outcomes, Scramble learning model, social science.